Menumbuhkan Semangat Jiwa Wirausaha Pemuda Karang Taruna Pondok Ranggon – Jakarta Timur di Era Digital - Rosalina; Santi Octavia; Andi Primafira (Jurnal Abdimas Ekonomi dan Bisnis, 2022)
In today's Digital era, it is very important to build the business character or entrepreneurshipof the younger generation. For them to have the awareness of changing the culture of 'jobseeking' to a culture of 'creating jobs and jobs'. The spirit of the entrepreneur must be in theyouth. One of them, built through carkater entreprenership by fostering new creativeentrepreneurs who are innovative based on technology.The purpose of this activity is toempower Karang Taruna Pondok Ranggon – East Jakarta by providing Education andMotivation to grow their entrepreneurial spirit through a series of interactive presentations anddiscussions. The results of this activity show that this activity is able to increase and foster theentrepreneurial spirit of the youth so that they have a sense of interpreneuership and are ableto see business opportunities. Keywords: Digital Era, Business Character, Entrepreneurship